Timely Recognition and Early Multi-Step Antinflammatory Therapy May Prevent ICU Admission of Patients With MIS-C: Proposal for a Severity Score - Brisca, Giacomo; Consolaro, Alessandro; Caorsi, Roberta; Pirlo, Daniela; Tuo, Giulia; Campanello, Claudia; Castagnola, Elio; Moscatelli, Andrea; Gattorno, Marco; Ravelli, Angelo (Frontiers in Pediatrics, 2021)
In this observational study, we report the clinical, therapeutics and outcome features of 23 patients with multisystem inflammatory syndrome (MIS-C) who have been treated in Gaslini Children Hospital (Genoa, Italy) with a multistep antinflammatory treatment protocol, based on disease severity at admission. Patients were initially assigned to four severity classes on admission and treated accordingly. The therapeutic options ranged from IV immunoglobulin alone to a combination of IVIG plus pulses of methylprednisolone plus anakinra for patients with marked cardiac function impairment or signs of macrophage activation syndrome, with rapid treatment escalation in case of inadequate therapeutic response. With the application of this therapeutic strategy, no patient required admission to Intensive Care Unit (ICU) or invasive mechanical ventilation, and no inotropic drugs administration was required. Conclusion: early aggressive treatment of MIS-C, with therapeutic interventions modulated based on the severity of clinical manifestations may help to prevent the progression of the inflammatory process and to avoid the need of admission to the ICU. A timely intervention with anti-IL-1 blockers can play a pivotal role in very severe patients that are at risk to have an incomplete response to immunoglobulins and steroids.